Isolation and characterisation of entomopathogenic fungi - Kwinda, Fhatani (University of the Witwatersrand, Johannesburg, 2024)
The purpose of the study was to isolate and identify fungal isolates in soil samples, followed by virulence characterisation to study their effectiveness in controlling insect pests using Tenebrio molitor as our model organism. Lastly, a combination study was conducted to evaluate the effectiveness of the joint use of two entomopathogenic microorganisms. For isolation, T. molitor was used as bait then the isolated fungal isolates were identified using molecular and morphological characterisation. Morphological characterisation included macroscopic (fungal cultures) and microscopic (conidia shape and size) analysis while molecular characterisations included extraction of DNA, amplification of the internal transcribed spacer region and sequence alignment. Once identification was done, virulence was assessed through in-vitro virulence parameter like vegetative growth and in-vivo assessment where bioassays were done against T. molitor. Lastly, entomopathogenic fungi were combined with Cruznema sp. NTM-2021 in a soil assay. From the study, two of the five isolates were identified as entomopathogenic fungi, Metarhizium anisopliae ARSEF 7487. M. anisopliae had the slowest vegetative growth but was the highest in virulence. When used for a single application in a soil environment it reaches 97.8% mortality and its combination with Cruznema sp. NTM-2021 resulted in a 57.8% mortality and an additive interaction. In conclusion, M. anisopliae used alone was effective in its control of T. molitor
A dissertation Submitted in fulfillment of the requirements for the degree Masters of Science In Molecular and Cell Biology In the Faculty of Science, University of the Witwatersrand, Johannesburg, South Africa, 2024
Keywords: Fungi; Entomopathogenic; Metarhizium; Biological agent; Virulence; UCTD; SDG-15: Life on land